(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2025)
The growing environmental impact of petroleum-based plastic packaging has intensified the need for biodegradable and sustainable alternatives. Among these, bacterial cellulose stands out as a promising biomaterial due to its remarkable purity, mechanical strength, and nanofibrillar structure. Unlike plant-derived cellulose, bacterial cellulose is naturally synthesized by specific bacteria in a form free from lignin and hemicellulose, making it highly suitable for use in eco-friendly packaging and biomedical applications. This review highlights recent advances in the biotechnological valorization of plant biomass, particularly agricultural residues such as straw, stalks, and husks, for bacterial cellulose production. These lignocellulosic feedstocks are abundant, renewable, and offer significant potential as substrates for microbial fermentation. The paper explores the chemical composition of various biomass types and evaluates their suitability for bacterial cellulose synthesis based on their cellulose, hemicellulose, and lignin content. In addition, the review outlines the enzymatic steps involved in bacterial cellulose biosynthesis and the microbial strains primarily responsible for its production. Together, these insights provide a scientific foundation for converting plant-based waste into biodegradable cellulose-based materials, contributing to the development of sustainable packaging solutions and supporting the transition toward a circular bioeconomy. Keywords: bacterial cellulose; lignocellulosic biomass; sustainable packaging; agricultural residues; microbial fermentation